Diversity in the school: Examining how teachers and school principles think about students with different socio-cultural background - Rayman, Julianna (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The following research aims to discover Roma/Gypsy and disadvantaged pupils situation in the school context by examining teachers and directors -prejudiced- thinking towards them. The fi rst part of the article focuses on teachers’ (n=1369) questionare data analyzis and results the separation of three thinking style. The thinking patterns are divided by the teachers relations toward Roma/Gypsy and disadvantaged pupils, furthermore by the level of responsibility what the teachers are claiming for themselves in their work with the students. The second half of the research explores the connection between school directors’ (n=21) and teachers’ (n=277) prejudiced thinking by examining interviews and questionare data. To sum up, the article is helping the get a clearer point of view about the possible patterns behind prejudices in the school context.